Effect of Fructose Levels in Diluents Citric Acid Egg Yolk on The Quality of Liquid Boar Semen Landrace - Mallo, Agustinus; Nalley, Wilmientje Marlene; Bette, Yustiani Yuliana (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
The aim of the research was to test the addition of fructose (F) in egg yolk citrate diluent (C-EY) on the quality of liquid semen from Landrace pigs during storage. This research used a completely randomized design method consisting of five treatments and five replications. The treatments in question are P0 (0%F), P1 (0.5%F), P2 (1.0%F), P3 (1.5%F) and P4 (2.0%F). The diluted cement is stored at a temperature of 18-20oC. Evaluation of the motility, viability, abnormalities and survival of spermatozoa is carried out every twelve hours. Analysis of variance (ANOVA) of data using SPSS. 25 for windows. The results showed P3 at 12 hours (80.00 ± 0.00%), 24 hours (74.00 ± 2.24%), 36 hours (62.00 ± 2.74%), 48 hours (41.00 ±2.24%) and spermatozoa were able to survive 48 hours of storage. P3 gave the best results (P<0.05) compared to other treatments with motility values of 41.00 ± 2.24%, viability 45.20 ± 1.64%, abnormalities 8.20 ± 1.10% and survival 51.20±3.05 hours. It was concluded that the addition of 1.5% fructose level in the egg yolk citrate diluent could maintain the quality of liquid semen longer than other treatments.